Investigation of Th17 cell differentiation in immunodeficiencies associated with high IgE levels and/or autoimmunity - AKKOÇ, TUNÇ; ÖĞÜLÜR, İSMAİL; AYDINER, ELİF; BARIŞ, SAFA (My University, 2011)
Objective: Hyper IgE Syndrome (HIES) and Common Variably Immunodeficiency (CVID) are immuno-deficiency diseases. HIES is characterized by recurrent skin abscesses, pneumonia, mucocutaneous fungal infections, eczama, eosinophilia and high serum IgE levels. CVID is characterized by recurrent bacterial infections in airways and gastrointestinal tract. In this study, differentiation of Th17 cells were aimed to be investigated in CVID and HIES patients.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); HIES; CVID; immunodeficiency; Th17